Combined loading of spudcan foundations on clay: numerical modelling - Martin, C; Houlsby, G (2001)
The load-displacement response of a spudcan foundation on clay is described by means of an incremental plasticity model with three degrees of freedom (vertical, rotational, horizontal). The model is termed 'Model B' and employs a yield surface and flow rule that are derived from a programme of carefully controlled small-scale laboratory tests. Behaviour inside the yield surface is defined by a set of elastic stiffness factors for embedded conical footings, determined from three-dimensional finite element analysis. The hardening law, which defines the vertical bearing capacity as a function of plastic spudcan penetration, is based on a set of theoretical lower bound bearing capacity factors for embedded conical footings. Care is needed to ensure consistent treatment of partially and fully penetrated spudcans under combined loading. Full details of the elastic and elasto-plastic stiffness matrices needed to predict incremental load-displacement behaviour are provided, and the performance of the model is demonstrated by simulating some of the laboratory calibration tests numerically. While Model B succeeds in capturing many important features of the observed spudcan behaviour, its prediction of sudden rather than gradual yielding is a noticeable weakness, particularly in the simulation of cyclic loading events. Practical applications of the foundation model are discussed with reference to the soil-structure interaction analysis of independent leg jack-up units.